Body height of elite basketball players: Do taller basketball teams rank better at the FIBA World Cup? - Zaric, I.; Kukic, F.; Jovicevic, N.; Zaric, M.; Markovic, M.; Toskic, L.; Dopsaj, M. (International Journal of Environmental Research and Public Health, 2020)
Body height is among the most important attributes of basketball players. Whether it differs among the basketball players who compete at the world basketball championship (FIBA-WC) is unknown. The aim of this study was to investigate the differences between the basketball players from the teams ranked 1-16 and those ranked below 16th place. The body heights of all players from the last three FIBA-WCs were collected and allocated according to the ranking at the FIBA-WC and analyzed by position in team. An independent sample t-test was conducted to analyze the difference in body height of players ranked 1-16 and players who ranked below 16th place. The players from the first 16 teams were significantly taller at three positions: point guards (Difference = 2.92 cm, p < 0.05), shooting guards (Difference = 2.16 cm, p < 0.05), and small forwards (Difference = 2.49 cm, p < 0.01). Body height seems to be an important factor for the performance of the basketball team at the FIBA-WC. Considering that all players at the FIBA-WC went through rigorous selection process to be in their national teams, body height of the higher-ranked players could be used as a reference value.